Chasing Self‐Assembly of Thioether‐Substituted Flavylium Salts in Solution and Bulk State. Issue 13 (17th May 2022) - Knöller, Julius A.; Forschner, Robert; Frey, Wolfgang; Lang, Johannes; Baro, Angelika; Zens, Anna; Molard, Yann; Giesselmann, Frank; Claasen, Birgit; Laschat, Sabine
Abstract: Two series of flavylium triflates carrying alkoxy side chains in the A‐ring (benzo unit of chromylium salt) and thioethers in the B ring (phenyl unit) (On ‐Fla ‐Sm ) as well as thioethers at both A and B ring (Sn ‐Fla ‐Sm ) were synthesized in order to understand the effect of thioether functionalization on their self‐assembly and electronic properties. Concentration‐dependent and diffusion ordered (DOSY) NMR experiments of O1 ‐iV ‐Fla ‐S3 indicate the formation of columnar H‐aggregates in solution with antiparallel intracolumnar stacking of the AC unit (chromylium) of the flavylium triflate, in agreement with the solid state structure of O1 ‐V ‐Fla ‐S1 . Thioether substitution on the B ring changes the linear optical properties in solution, whereas it has no effect on the A ring. According to differential scanning calorimetry, polarizing optical microscopy and X‐ray diffraction bulk self‐assembly of these ionic liquid crystals (ILCs) depends on the total number of side chains, yielding SmA and LamCol phases for ILCs with 2–3 chains and Colro, Colh phases for ILCs with 3–6 chains. Thus, we demonstrated that thioethers are a useful design tool for ILCs with tailored properties. Abstract : Sulfur for stability ! The more sulfur the better columnar phases are stabilized in flavylium ILCs. In solution thioethers particularly at the B ring exert an auxochromic effect on the absorption spectra and lead to antiparallel columnar stacking.